Where are the female developers? Exploring the gender issues in open source software innovation process - Mahmod, Musyrifah; Mohd Yusof, Shafiz Affendi; Md Dahalin, Zulkhairi (2010)
Despite the growing literature on Open Source Software (OSS) innovation, knowledge about gender issues within the OSS innovation process is inadequate.This paper begins with some introduction on OSS innovation process, it then continues with the discussion of the current problems on gender and OSS innovations.The paper argues that appropriate feminist approach may be useful in augmenting the understanding of OSS innovation process through the lens of social constructivist’s theory.Finally, the paper summarized with some preliminary consideration of how these concerns may be applied to OSS innovation process.